Fucoidan Extracted from Undaria pinnatifida: Source for Nutraceuticals/Functional Foods - Yu Zhao; Yizhou Zheng; Jie Wang; Shuyi Ma; Yiming Yu; William Lindsey White; Shiping Yang; Fan Yang; Jun Lu (Marine Drugs, 2018)
The importance of fucoidan as a functional ingredient in food, health products, and pharmaceutics is well-recognized due to its beneficial biological effects. Fucoidan is usually extracted from brown seaweeds, including Undaria pinnatifida. Fucoidan exhibits beneficial bio-activity and has antioxidant, anticancer, and anticoagulant properties. This review focuses on the biological activity of U. pinnatifida-derived fucoidan and investigates its structure–activity or fraction–activity relationship. It also describes several fucoidan extracts, along with their claimed anticancer effects. It aims to provide information and thoughts for future research such as the development of fucoidan into functional foods or nutraceuticals.